PENINGKATKAN KEMAMPUAN KARANGAN MENULIS KARANGAN ESKPOSISI DENGAN MENGGUNAKAN MEDIA WALL CHART - Andi Paida (Universitas Negeri Makassar, 2020)
Improving the Ability to Write Exposition Essay Using Wall Chart Media. The purpose of this study was to improve the ability to write exposition essay using wall chart media. This research is a classroom action research. The population in this study was grade X students of SMK Negeri 9 Bulukumba. The results showed that the use of wall chart media in exposition writing learning can improve student learning outcomes in cycle II. In addition, the use of wall chart media can increase student activity in the learning process.